2021
DOI: 10.5534/wjmh.190158
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy in Men with Untreated or Treated Prostate Cancer: Do We Have Enough Evidences?

Abstract: Purpose To investigate the oncologic safety of testosterone replacement therapy (TRT) in men with untreated or treated prostate cancer. Materials and Methods We systematically searched PubMed, Embase, and Cochrane library database from January 1941 to March 2019. Results In total, 36 articles met the eligibility criteria for this systematic review. They included a total of 2,459 TRT-treated patients, with a median of 20 patients per study (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In recent years, the morbidity of PCa has increased [17]. In 2018, approximately 1,300,000 PCa cases were newly reported worldwide, accounting for 13.5% of the morbidity of malignant tumors in males, and approximately 360,000 deaths occurred, accounting for 6.7% of cancer mortality for male patients [18]. Patients are often in an advanced stage of PCa when they are diagnosed due to the lack of significant early symptoms [6].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the morbidity of PCa has increased [17]. In 2018, approximately 1,300,000 PCa cases were newly reported worldwide, accounting for 13.5% of the morbidity of malignant tumors in males, and approximately 360,000 deaths occurred, accounting for 6.7% of cancer mortality for male patients [18]. Patients are often in an advanced stage of PCa when they are diagnosed due to the lack of significant early symptoms [6].…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, in hypogonadal men on AS for low stage/grade PC, the current body of evidence supporting TRT is restricted to a few small, retrospective observational studies. Taken together, these studies are not conclusive regarding the safe use of TRT in hypogonadal men on AS, as some studies reported high progression rates for patients on TRT during AS [ 147 ]. Prospective randomized clinical trials in this field are needed.…”
Section: Prostate Health In Men With Trtmentioning
confidence: 99%
“…Also, for radiotherapy, the sparse data available does not show that the use of TRT increase the risk of worsen PC severity. In a recent systematic review of available literature [ 147 ], eight out of nine included studies showed that TRT-treated patients with PC treated by radiation therapy did not have an increased risk for disease progression. However, the overall quality of available evidence is poor and prospective controlled studies are lacking.…”
Section: Prostate Health In Men With Trtmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review of 36 studies, including 2459 testosterone‐treated patients found that testosterone treatment is not associated with increased risk of disease progression in prostate cancer 136 . The quality of studies included was poor though, with no level 1 evidence.…”
Section: Screening For Prostate Cancer In Men During Testosterone Therapymentioning
confidence: 99%